Gut microbiota–derived metabolites in immunomodulation and gastrointestinal cancer immunotherapy - Luo, Wenbin; Li, Ruoyun; Pan, Chaofan; Luo, Changjiang (Frontiers in Immunology, 2025)
Gut microbiota-derived metabolites have emerged as critical mediators linking microbial composition with immune regulation and tumor progression in gastrointestinal (GI) cancers. This review highlights four major classes of metabolites: short-chain fatty acids (SCFAs), bile acids, tryptophan derivatives, and several emerging metabolites such as inosine, trimethylamine-N-oxide (TMAO), and urolithin A. These metabolites exert context-dependent effects by modulating innate and adaptive immune cells, shaping the tumor microenvironment, and influencing inflammatory and epigenetic pathways. Importantly, their immunoregulatory effects are not confined to the intestinal milieu but can extend systemically through both cellular and chemical routes. SCFAs and urolithin A enhance epithelial barrier integrity and CD8+ T cell activity but may also promote immune tolerance. Bile acids display dual roles, with ursodeoxycholic acid and tauroursodeoxycholic acid counteracting the tumor-promoting effects of deoxycholic acid and lithocholic acid. Tryptophan metabolism produces both immunosuppressive (kynurenine) and immune-protective (indole derivatives) metabolites that regulate T-cell differentiation and function. In addition, dietary interventions, probiotics, engineered microbes, and plant-derived nanoparticles offer novel strategies to reshape the microbiota–metabolite–immune axis and improve immunotherapy outcomes. To pinpoint the sites of metabolite action and mitigate translational risks, we highlight immune-competent organoid co-culture systems. These platforms enable quantitative assessment of exposure–response thresholds, dissection of context-dependent effects, and in vitro pre-evaluation of the feasibility and safety of metabolite-based immunologic adjuvants combined with PD-1/PD-L1 blockade. Collectively, microbiota-derived metabolites represent promising targets for precision diagnosis and treatment in GI cancer immunotherapy.